The Subject, Functions and Basic Methods of History - Ghazaryan, Albert (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
One of the most important issues concerning the methodology of history is what the subject of Social History is and which the functions of it are. Under Social History the article refers to the society of the past, the human, his individuality in social, political, economic, psychological, cultural planes, their change in space and time. Here the disclosure, description, and explanation of the peculiarities of natural changes can be stated. The article presents the scientific-cognitive and educational functions of History. In addition, History serves as public memory and contributes to foresight.
Keywords: History, the subject of History, function, Social History, formation, scientific cognition, foresight, memory, education